The demographic profile, clinical spectrum, and outcome of term neonates requiring continuous positive airway pressure in a tertiary care teaching hospital - Salib Hamid; Naik, Suhail Ahmad; Shafat Tak (Asian Journal of Medical Sciences, 2024)
Background: Respiratory distress is the major cause of neonatal intensive care unit (NICU) admission of full-term neonates for which they require different levels of mode of ventilation. Aims and Objectives: The objective of this study was to determine the demographic profile, clinical spectrum, and outcome of term neonates, requiring continuous positive airway pressure (CPAP) in tertiary care teaching hospitals. Materials and Methods: The study was a prospective observational study conducted from December 2020 to November 2022 in the neonatal section of the department of pediatrics. Results: A total of 261 neonates were included in the study. The male-to-female ratio was 1.7:1, the range of birth weight was between 2.1 kg and 3 kg (60.91%), the gestation age was 38 weeks (59.2%), and 73.6% were lower-segment cesarean section born. The age of starting CPAP in most of the newborns was at admission to NICU (in 69.73% of cases). The success rate of CPAP therapy was high (60.9%) and the rest 39.08% of patients did not settle with CPAP and required higher modes of respiratory support such as nasal intermittent positive pressure ventilation (IPPV) (5.89%) and IPPV (94.11%). Conclusion: In the resource-limiting settings, due to the non-availability of higher levels of ventilatory gadgets, the early use of CPAP as a mode of ventilation in full-term babies with transient tachypnea of newborns is well-documented and it can be safely used in other common neonatal conditions which can cause respiratory distress in full-term neonates. The low-middle-income countries are facing challenges to improve comprehensive neonatal care; there is a dire need for simple and cost-effective methods of respiratory support. Bubble CPAP is one such promising ventilatory support intervention, which may reduce the need for costly mechanical ventilators.